Who Has Done It? Exploring Gaze Agency in Obsessive-Compulsive Checkers - Giuliani, Mattia; Martoni, Riccardo M.; Gregori Grgič, Regina; Crespi, Sofia A.; Cavallini, Maria C.; de’Sperati, Claudio (Frontiers in Integrative Neuroscience, 2017)
The sense of agency (SoA) is a multifaceted construct, which can be defined as the ability to understand the causal relationships between our actions and sensory events. Obsessive-Compulsive Disorder (OCD) patients with checking compulsions often report a “lack of action completion” sensations, which has been conceptualized in the so-called “Not Just Right Experiences” construct. An intriguing explanation of this phenomenon comes from Belayachi and Van der Linden (2009, 2010), who suggest that OCD-checking patients are more prone to specify their action in a relatively molecular and inflexible way. Currently, there are no studies in literature which address this issue in OCD patients, except for the one of Gentsch and colleagues (2012), who suggested an altered SoA in these patients. Here we exploited a novel construct, gaze agency, to evaluate causal attribution capabilities in a group of 21 OCD patients (checkers) and matched healthy controls (HCs). Basically, two tasks targeted observers’ capability to identify their own eye movements as the cause of concurrently presented beeps, which allowed us to measure agency sensitivity as well as subtle agency alterations in an ecological setting. We found a poorer performance in OCD patients as compared to HCs in many parameters of our tasks, suggesting a difficulty with causal attribution possibly due to both a reduced cognitive flexibility and a less functional gaze agency in OCD patients.